9000 years of human lakeside adaptation in the Ethiopian Afar: Fisher-foragers and the first pastoralists in the Lake Abhe basin during the African Humid Period. (1st September 2020) - Khalidi, Lamya; Mologni, Carlo; Ménard, Clément; Coudert, Lucie; Gabriele, Marzia; Davtian, Gourguen; Cauliez, Jessie; Lesur, Joséphine; Bruxelles, Laurent; Chesnaux, Lorène; Redae, Blade Engda; Hainsworth, Emily; et al.
Abstract: In this study, new approaches are developed for measuring and understanding the reactivity of East African amplifier lakes and the societies that occupied their margins to African monsoon related hydrological changes. Drawing on seven newly discovered archaeological sites in the Lower Awash valley, corresponding to the northern Abhe Lake basin, we present the first Holocene human occupation sequence in the Ethiopian Afar. We reconstitute fluctuating Abhe Lake levels in association with human settlement strategies through correlation of new archaeological and geomorphological data and 37 new radiocarbon dates. The sites cluster into three periods of human occupation of the lake margins separated by intervals that lack archaeological data. These occupation phases span two major humid-arid transitions of the African Humid Period (AHP) (including the Younger Dryas (YD, ∼12.9–11.7 ka), 8.2 ka, and 4.2 ka arid events) during which Abhe Lake levels varied significantly, and the transition from Later Stone Age (LSA) hunter-gatherers to mixed herding-hunter-gatherer economies. Over a 9000 year period we observe continuity and ruptures in subsistence strategies and material culture techno-complexes and correlate these with sedimentary formation processes and changing paleo-shorelines. Our study reveals that flexible multiple resource economies were a human response to strongly fluctuating environments, even with the onset of herding and associated pottery traditions unique to the Abhe Lake basin, sometime between 4.8 and 3.3 ka cal. BP. Thorough evaluation of littoral morpho-sedimentary data, well-dated human settlements and associated economic strategies suggests that major cultural and socio-economic changes of populations inhabiting Abhe paleolakeshores were distinctive ecological responses to transformations in the local environment and to fluctuating lake levels. Highlights: First evidence of Later Stone Age to herding transition in the Ethiopian Afar. Revision of Abhe Lake level curve and modelling of Holocene paleoshorelines. Human occupation of lake margins during humid-arid transitions of African Humid Period. Signal for onset of aridification at 8.4 ka and imprint of 4.2 ka event in the Afar. Humans responded to strongly fluctuating environments with flexible mixed economies.